Electromagnetic Thermal Noise in Upper‐Hybrid Frequency Range. Issue 7 (7th July 2018) - Yoon, Peter H.; Hwang, Junga; López, Rodrigo A.; Kim, Sunjung; Lee, Jaejin
Abstract: The inner magnetosphere including the radiation belt and ring current environment is replete with high‐frequency fluctuations with peak intensity occurring near upper‐hybrid frequency and/or multiple harmonic electron cyclotron frequencies above and below the upper‐hybrid frequency. Past and contemporary spacecraft missions, including the Van Allen Probes, were designed to detect the electric field spectrum only for these high‐frequency fluctuations. Making use of the recently formulated generalized theory of electromagnetic spontaneous emission in thermal magnetized plasmas, it is shown that upper‐hybrid/multiple harmonic electron cyclotron emissions are characterized by a significant magnetic field component, even in the high‐frequency regime. Such a prediction may potentially be tested by upcoming spacecraft missions including the Solar Probe Orbiter and Parker Solar Probe. The present finding may also have a potentially significant ramification for the broader astrophysical contexts. Plain Language Summary: The upcoming National Aeronautics and Space Administration mission to inner heliosphere Parker Solar Probe and similar European Space Agency mission Solar Orbiter have nearly identical instruments to measure high‐frequency electromagnetic signals in space. The present paper makes a prediction that high‐frequency signal known as the thermal noise may contain significant magnetic field component. In the past, thermal noise was considered to be made of electrostatic signals only. The National Aeronautics and Space Administration and European Space Agency spacecraft may test the predictions made in the present paper. The potential significance of the present work may also be related to efforts to find exoplanets with magnetosphere. Electromagnetic thermal noise, if it is intense enough, may be detected remotely by highly sensitive radio receivers. Key Points: Upper‐hybrid and nice fluctuations are pervasively measured in the inner magnetosphere, including the radiation belt Past and contemporary space missions, including the Van Allen Probes, are capable of measuring the electric field spectrum only The magnetic field fluctuation spectrum may be measured by the Parker Solar Probe and Solar Orbiter